APLIKASI PEMESANAN PADA TOKO SABLON BAJU MENGGUNAKAN METODE RAPID APLICATION DEVELOPMENT - Sugeng, Jonny Kurniawan; Ikrimach, Ikrimach (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
In today's digital era, advancements in information technology have had a significant impact on various sectors, including the business world. "Sablon Yogyakarta," a store offering custom t-shirt printing services, faces challenges in accommodating its expanding customer base, especially in handling orders and managing customer data. The current manual ordering process has proven to be inefficient, prone to errors, and susceptible to delays in processing orders and providing timely confirmations. This inefficiency can affect customer satisfaction and limit the store's operational effectiveness. To address these issues, there is a pressing need for a web-based ordering system that allows customers to place custom t-shirt orders online, easily selecting designs, sizes, and printing preferences. This system will streamline the order process, reduce human error, and enable better management of order and customer data. Additionally, it will facilitate faster communication between the store and customers, enhancing overall service quality and ensuring smoother transaction processes.